The interplay between feelings and beliefs about condoms as predictors of their use. Issue 2 (1st February 2018) - Ellis, Erin M.; Rajagopal, Rekha; Kiviniemi, Marc T.
Abstract : Objective: Negative feelings about condoms are a key barrier to their use. Using the behavioural affective associations model, we examined the joint effects of affective associations and cognitive beliefs about condoms on condom use. Design: In Study 1 ( N = 97), students completed measures of their affective associations and cognitive beliefs about sex and condoms, sexual activity and condom use. In Study 2 ( N = 171), a measure of behavioural intentions and condom selection task were added. Main outcome measures: Condom use measured in Study 1 as (1) current condom use, and (2) willingness to use condoms; in Study 2 as: (1) behavioural intentions, (2) number of condoms selected. Results: Affective associations with sex and condoms were behaviour-specific, were directly associated with the respective behaviour, and mediated the relations of cognitive beliefs to behaviour, ps < .05. In Study 2, affective associations were associated with behavioural intentions and the number of condoms selected, ps < .05; cognitive beliefs were indirectly associated with these outcomes through affective associations, indirect effects : ps < .05. Conclusions: Affective associations are a behaviour-specific and proximal predictor of condom use, mediating the effect of cognitive beliefs, suggesting they may be a particularly viable intervention target.